Polyamine patterns in haploid and diploid tobacco tissues and in vitro cultures - Carone,Sílvia Bicudo (2010)
The aim of this work was to determine PAs levels in pith tissues and callus cultures from haploid and diploid tobacco plants, explanted from the apical and basal regions of the stem. These explants were cultured in an RM-64 medium supplied with IAA and kinetin, under light or in the dark, during successive subcultures. PAs levels followed a basipetal decrease in diploid and an increase in haploid, pith tissues. A similar pattern of total PAs (free + conjugated) was observed for the callus of diploid and haploid plants maintained in the light, and for the haploid callus in the dark, whereas the diploid callus in the dark showed a constant increase in total PAs levels until the end of culture. The PA increase in the diploid callus in the dark was related to free Put levels increase. The ploidy status of the plants could express different PA gradients together with the plant pith and in vitro callus cultures.